A process of reverse electrodialysis (RED) coupled with water electrolysis (WE) for air conditioning waste heat recovering: A conceptual design. Issue 1 (September 2020) - Li, Yaxiao; Yang, Dongxiao
Abstract: Air conditioning waste heat deserves attention for its abundance, especially for the large-scale industrial and commercial systems. Hydrogen is widely accepted as an ideal energy carrier in the foreseeable future. In this paper, a process combining reverse electrodialysis (RED) and water electrolysis (WE) is proposed to convert the air conditioning waste heat to the hydrogen energy. Based on the assumption of large-scale application of the fuel cell electrical vehicle (FCEV), a conceptual design of the proposed process is investigated. The RED section of the process consumes both the air conditioning waste heat and the solar energy to generate electrical power, while the WE section produces hydrogen by using the electrical power. The concentration of the artificial brine solution for RED is designed to be 4-5 M, and its operating temperature is set to 40 °C. The RED power density in this paper is assumed to be 2.7 W/m 2 Furthermore, a techno-economic analysis is carried out for the process. Results showed that the proposed process shows potential to become an alternative option for air conditioning waste heat recovery. The conclusion of this paper may be interesting to the researchers in the fields of RED technology and low-grade heat recovery.